AN ECONOMIC STUDY OF THE ITEMS OF PRODUCTION AND MARKETING COSTS FOR THE ORANGE CROP IN SALAH AL-DIN GOVERNORATE FOR THE PRODUCTION SEASON (2022) BALAD DISTRICT AS A MODEL)) - Amna Hamid Mayouf; Dr. Firas Ibrahim Arhim (American Journals, 2023)
The main objective of the study of the orange crop is to identify the most important marketing functions from the producer until reaching the final consumer, and to estimate the marketing costs of the orange crop in the area under study for the year (2022), where a stratified random sample consisting of (65) farmers from the district’s farmers was selected. Information related to the study through a questionnaire designed for farmers, and then collecting information on wholesale markets through a questionnaire number (35) distributed to wholesale market traders, while information on retail markets was also collected through a questionnaire number (35) distributed to retailers, As the share of the producer, wholesaler, and retailer of the consumer’s dinars of the orange crop, respectively, was about (77.47%), (16.21%), (6.30%). The marketing costs for each of the producer, the wholesaler, and the retailer, respectively, amounted to (28.100, 44.9, and 21.86 dinars / ton). We conclude from this that the high marketing costs cause lower profits. We conclude from this and recommend the study to give sufficient importance to scientific research and intensify studies related to the orange crop Such as production, its costs, and marketing. It recommends the need to develop integrated strategic plans for agricultural marketing, which begins before production and purchase of seedlings, and ends with the arrival of the product from standard premiums to the final consumer.
Keywords: Economic study, Production costs, Marketing costs, Orange crop, Cost analysis